Polyurethane noise reduction spillplate and preparation method thereof
By adding graphene, toughening agents, wear-resistant agents and microbeads to the polyurethane coal blocking board, the problem of low wear resistance and toughness of the polyurethane coal blocking board is solved, achieving higher impact strength and longer service life. life.
Patent Information
- Application Number
- CN202411454882.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The existing polyurethane coal barrier plates have low wear resistance and toughness, making it difficult to meet the needs of high impact resistance and long-term friction and wear.
By adding graphene, toughening agents, wear-resistant agents and microbeads, and controlling the amounts of each component, the mechanical properties and wear resistance of polyurethane materials can be improved.
Significantly improves the toughness and impact strength of the polyurethane coal blocking board, extends its service life, and improves its wear resistance and sound absorption performance.
Smart Images

Figure BDA0005090167220000071 
Figure BDA0005090167220000081 
Figure BDA0005090167220000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal retaining plates, and in particular to a polyurethane noise reduction coal retaining plate and a preparation method thereof. Background Art
[0002] With the advancement of coal mining technology, machine-mined coal has now developed into a comprehensive mechanized and even automated operation. However, in thin coal seam mining areas where iron sulfide nodules are common in coal seams, it is difficult to use the pick of the coal mining machine to cut due to the high hardness of the nodules. Therefore, the blasting coal dropping process has been widely used. The coal discharge process of blasting coal dropping is labor-intensive and time-consuming. The use of scraper conveyors to discharge coal is currently a common practice. The coal baffle, an important device installed on the pipe guard near the side chute of the scraper conveyor near the goaf, is used to resist the coal rushing towards the goaf during blasting coal dropping. It is a key component for recovering floating coal into the scraper conveyor to avoid resource loss.
[0003] The current coal mining operations have extremely high requirements for coal baffles. Construction sites that use blasting to drop coal require that the coal baffles be able to withstand the instantaneous impact of blasting, have a certain impact strength, and are not prone to plastic deformation. At the same time, during the automated transportation process, they must withstand long-term friction and wear, avoid frequent replacement, and improve production efficiency and safety. Therefore, the coal baffles need to have good impact resistance, wear resistance, sound absorption and other properties to increase the reuse rate of the coal baffles. Polymer polyurethane and polyethylene materials are the main raw materials for the production of coal baffles. However, the wear resistance and toughness of polyurethane materials are relatively low, and the polyurethane matrix needs to be effectively modified to extend the long-term service capacity of the coal baffles. Summary of the invention
[0004] The main purpose of the present invention is to provide a polyurethane coal retaining plate and a preparation method thereof, so as to solve the problems of low wear resistance and toughness of the polyurethane coal retaining plate in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a polyurethane coal barrier is provided, which comprises the following components in parts by weight: 100 parts of polyurethane, 2 to 6 parts of graphene, 0.01 to 0.5 parts of cross-linking agent, 1 to 8 parts of wear resistance agent, 5 to 25 parts of toughening agent, 0.1 to 1 parts of processing aid, and 1 to 9 parts of microbeads.
[0006] Furthermore, the mass ratio of graphene to toughening agent is (4-6):(5-25).
[0007] Furthermore, the weight average molecular weight of the polyurethane is 70,000 to 100,000, the melt index is 2 to 3 g / 10 min, and the glass transition temperature is 100 to 130° C.
[0008] Furthermore, the density of polyurethane is 1.085-1.293 g / cm 3 , melting point is 160~190℃.
[0009] Furthermore, the crosslinking agent is at least one of polyetherimide, polyallylamine, polydopamine, polyesterimine, trishydroxymethylaminomethane, polystyrene-divinylbenzenesulfonic acid, and γ-aminopropyltriethoxysilane.
[0010] Furthermore, the wear-resistant agent is at least one of polytetrafluoroethylene, molybdenum disulfide, polysiloxane, glass fiber, carbon fiber, and aramid fiber.
[0011] Furthermore, the processing aid is at least one of dibasic lead phosphite, methyl tin, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2,6-di-tert-butyl-4-methylphenol.
[0012] Furthermore, the microbeads are at least one of organic microbeads and inorganic microbeads.
[0013] Furthermore, the toughening agent is a compound of a first toughening agent and rubber; the first toughening agent is at least one of a polyolefin-based thermoplastic elastomer and a bio-based polyol; the bio-based polyol is at least one of vegetable oil, starch, and cellulose; and the rubber is at least one of natural rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber.
[0014] Furthermore, in the compound, the mass ratio of the first toughening agent to the rubber is (2-3):(1-3).
[0015] According to a second aspect of the present invention, a method for preparing a polyurethane noise reduction coal retaining plate is provided, comprising the following steps:
[0016] S1, adding graphite powder and a dispersant into water to obtain a first mixture, and preparing a graphene dispersion by using a liquid phase shear exfoliation technique on the first mixture;
[0017] S2, mixing the graphene dispersion with the crosslinker solution to obtain a second mixture, and subjecting the second mixture to microwave treatment to obtain crosslinker-modified graphene;
[0018] S3, mixing the cross-linking agent-modified graphene, the wear-resisting agent, the toughening agent, the processing aid, the microbeads and the polyurethane to obtain a third mixture, and performing injection molding on the third mixture to obtain a polyurethane noise reduction coal baffle.
[0019] Furthermore, in S1, the dispersant is at least one of N-methylpyrrolidone, sodium dodecylbenzenesulfonate, sodium taurodeoxycholate, dimethylformamide, ethanol, o-dichlorobenzene, and poloxamer; and the graphite is at least one of microcrystalline graphite, thermally expanded graphite, and highly oriented pyrolytic graphite.
[0020] Furthermore, in S1, the mass fraction of the dispersant in the graphene dispersion is 0.02% to 1%, and the mass fraction of the graphene in the graphene dispersion is 0.5% to 15%.
[0021] Furthermore, in S1, the instrument used in the liquid phase shear stripping technology is at least one of a nano-bead mill, a pin-type sand mill, a turbine sand mill, and a high-pressure homogenizer, and the conditions for liquid phase shear stripping are: 600-3200 r / min, 0.5-5h.
[0022] Furthermore, the first mixture is stirred before the liquid phase shear exfoliation technique is used.
[0023] Furthermore, the mass fraction of the crosslinking agent in the crosslinking agent solution is 0.01% to 0.5%, and in S2, the volume ratio of the graphene dispersion to the crosslinking agent solution is (5 to 50):1.
[0024] Furthermore, in S2, the microwave treatment conditions are: output power 350-5000 W, reaction temperature 50-180° C., and reaction time 1-40 min.
[0025] Furthermore, in S2, after microwave treatment, cross-linker-modified graphene is obtained by freeze drying.
[0026] Furthermore, in S3, the injection molding conditions are as follows: an injection molding machine injection pressure of 15 to 120 bar, a barrel temperature of 170 to 240° C., a mold temperature of 10 to 60° C., and an injection molding sheet thickness of 5 to 500 mm.
[0027] Furthermore, in S3, after injection molding, radiation cross-linking is performed to obtain a polyurethane noise reduction coal baffle.
[0028] Furthermore, the radiation source of the radiation cross-linking is at least one of a high-energy electron beam and Co-60, and the conditions of the radiation cross-linking are a radiation dose of 30 to 100 kGy and a radiation rate of 0.1 to 1 kGy / h.
[0029] By applying the technical solution of the present invention, by adding graphene and a toughening agent and controlling their dosage, the toughness of polyurethane can be significantly improved and its impact strength can be increased. In addition, by adding a wear-resistant agent, the wear resistance of the polyurethane material can be improved. In addition, by further adding microbeads and controlling their dosage, the various components can act synergistically, so that the polyurethane material has good wear resistance and impact strength, and its service life is extended. In addition, the present invention controls the components of the polyurethane noise reduction coal baffle and the dosage of each component, so that the sound absorption performance is good and the noise reduction effect is good. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] As described in the background technology of the present invention, there are problems in the prior art of low wear resistance and toughness of polyurethane noise reduction coal retaining plates. In order to solve the above technical problems, in a typical embodiment of the present invention, a polyurethane noise reduction coal retaining plate is provided, which comprises the following components in parts by weight: 100 parts of polyurethane, 2 to 6 parts of graphene, 0.01 to 0.5 parts of cross-linking agent, 1 to 8 parts of wear resistance agent, 5 to 25 parts of toughening agent, 0.1 to 1 parts of processing aid, and 1 to 9 parts of micro beads.
[0032] Graphene has a two-dimensional honeycomb lattice structure, and has the advantages of high strength, good toughness, easy loading of functional groups, and the ability to absorb and reduce noise. The compatibility between graphene and other fillers and matrices can be enhanced by adding a cross-linking agent. However, if the amount of graphene is too much, its dispersibility will be reduced, resulting in stress concentration inside the material, which will in turn reduce the overall performance of the polyurethane noise reduction coal barrier. By controlling its amount within the above range, and adding wear-resistant agents, toughening agents, microbeads and processing aids to regulate its amount, the various components can work synergistically, and the obtained polyurethane noise reduction coal barrier has good component uniformity, and its mechanical properties can also be significantly improved.
[0033] In some embodiments, the mass ratio of graphene to toughening agent is (4-6):(5-25).
[0034] By regulating the mass ratio of graphene and toughening agent, the toughness of the polyurethane noise reduction coal barrier plate can be effectively improved without significantly affecting the wear resistance of the polyurethane noise reduction coal barrier plate, and the plate has strong impact resistance and a long service life.
[0035] In some embodiments, the polyurethane has a weight average molecular weight of 70,000 to 100,000, a melt index of 2 to 3 g / 10 min, and a glass transition temperature of 100 to 130°C.
[0036] The molecular weight, melt index and glass transition temperature of polyurethane have a great influence on the processing performance and mechanical properties of polyurethane noise reduction coal baffle. By controlling the three within the above range, in the polyurethane noise reduction coal baffle system of the present invention, on the one hand, it is helpful to process a polyurethane noise reduction coal baffle with uniform composition, and on the other hand, it is helpful to prepare a polyurethane noise reduction coal baffle with high wear resistance and impact strength. In the present invention, the melt index is measured according to ASTM D1238 standard at 190°C and 2.16kg.
[0037] In some embodiments, the density of the polyurethane is 1.085 to 1.293 g / cm 3 , melting point is 160~190℃.
[0038] Controlling the density and melting point of the polyurethane within the above range helps to improve the processing performance and stability of the polyurethane noise reduction coal baffle. At the same time, it is easy to prepare a polyurethane noise reduction coal baffle with good mechanical properties using the above polyurethane as a matrix material.
[0039] In some embodiments, the crosslinking agent is at least one of polyetherimide, polyallylamine, polydopamine, polyesterimine, trishydroxymethylaminomethane, polystyrene-divinylbenzenesulfonic acid, and γ-aminopropyltriethoxysilane.
[0040] The cross-linking agent can play a good modification role on graphene, making it compatible with the wear-resistant agent, processing aid, microbeads, toughening agent and polyurethane in the present invention, and can be dispersed evenly, so that the advantages of graphene are fully exerted.
[0041] In some embodiments, the wear-resistant agent is at least one of polytetrafluoroethylene, molybdenum disulfide, polysiloxane, glass fiber, carbon fiber, and aramid fiber.
[0042] The above-mentioned wear-resistant agent has good dispersibility in the polyurethane material and can effectively improve the wear resistance of the polyurethane material.
[0043] In some embodiments, the processing aid is at least one of dibasic lead phosphite, methyl tin, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2,6-di-tert-butyl-4-methylphenol.
[0044] Adding the above properties can improve the stability of polyurethane materials and thus extend their service life.
[0045] In some embodiments, the microbeads are at least one of organic microbeads and inorganic microbeads, such as 920DET40d25 microbeads, soda lime borosilicate glass microbeads, silica-hydrogel microbeads, hollow glass microbeads, and the like.
[0046] The micro-beads can significantly improve the fluidity and processing properties of the polyurethane material, and can also improve its anti-aging properties. In addition, adding the micro-beads can also simultaneously improve the wear resistance and impact resistance of the polyurethane material.
[0047] In some embodiments, the toughening agent is a compound of a first toughening agent and rubber; the first toughening agent is at least one of a polyolefin-based thermoplastic elastomer and a bio-based polyol; the bio-based polyol is at least one of a vegetable oil, starch, and cellulose; the rubber is at least one of natural rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber. Furthermore, in the compound, the mass ratio of the first toughening agent to the rubber is (2-3): (1-3).
[0048] By selecting two types of toughening agents and controlling their ratio, the impact strength of the polyurethane noise reduction coal barrier can be significantly improved.
[0049] According to a second aspect of the present invention, a method for preparing a polyurethane noise reduction coal retaining plate is provided, comprising the following steps:
[0050] S1, adding graphite powder and a dispersant into water to obtain a first mixture, and preparing a graphene dispersion by using a liquid phase shear exfoliation technique on the first mixture;
[0051] S2, mixing the graphene dispersion with the crosslinker solution to obtain a second mixture, and subjecting the second mixture to microwave treatment to obtain crosslinker-modified graphene;
[0052] S3, mixing the cross-linking agent-modified graphene, the wear-resisting agent, the toughening agent, the processing aid, the microbeads and the polyurethane to obtain a third mixture, and performing injection molding on the third mixture to obtain a polyurethane noise reduction coal baffle.
[0053] Liquid phase shear exfoliation technology is a commonly used method for preparing two-dimensional materials. By applying shear force in the liquid phase, layered graphite materials can be exfoliated into single-layer or few-layer two-dimensional materials. This method is highly efficient and easy to scale up, and the obtained graphene dispersion has good uniformity. Microwave treatment can improve the cross-linking efficiency and prepare functionalized graphene, which is beneficial to improve the compatibility between graphene and other fillers and matrix polyurethane materials. The above method is simple in process and highly efficient, and can prepare a polyurethane noise reduction coal baffle with uniform composition.
[0054] In some embodiments, in S1, the dispersant is at least one of N-methylpyrrolidone, sodium dodecylbenzenesulfonate, sodium taurodeoxycholate, dimethylformamide, ethanol, o-dichlorobenzene, and poloxamer; and the graphite is at least one of microcrystalline graphite, thermally expanded graphite, and highly oriented pyrolytic graphite.
[0055] By selecting the types of the dispersant and graphite, the components in the prepared first mixture are highly uniform and free of precipitation.
[0056] In some embodiments, in S1, the mass fraction of the dispersant in the graphene dispersion is 0.02% to 1%, and the mass fraction of the graphene in the graphene dispersion is 0.5% to 15%.
[0057] Controlling the content of the dispersant can prepare a first mixture with a more uniform distribution of components. Controlling the content of graphene, that is, controlling the content of graphite, can, on the one hand, allow the graphite to be fully exfoliated, and on the other hand, improve the uniformity of the graphene dispersion.
[0058] In some embodiments, in S1, the instrument used in the liquid phase shear stripping technology is at least one of a nano bead mill, a pin sand mill, a turbine sand mill, and a high-pressure homogenizer, and the conditions for liquid phase shear stripping are: 600-3200 r / min, 0.5-5h.
[0059] In some embodiments, stirring treatment is performed before using the liquid phase shear stripping technology. The stirring time is 10 to 90 minutes. The uniformity of the first mixture is higher, which helps to improve the stripping efficiency.
[0060] In some embodiments, the mass fraction of the crosslinker in the crosslinker solution is 0.01% to 0.5%, and in S2, the volume ratio of the graphene dispersion to the crosslinker solution is (5 to 50):1.
[0061] The concentration of the cross-linking agent will affect the modification effect of the cross-linking agent on graphene, and will also affect the performance of graphene to a certain extent. By controlling the concentration of the cross-linking agent in the cross-linking agent solution and the volume ratio of the graphene dispersion and the cross-linking agent solution, the cross-linking agent-modified graphene obtained can effectively improve the mechanical properties of the polyurethane material.
[0062] In some embodiments, in S2, the conditions for microwave treatment are an output power of 350 to 5000 W, a reaction temperature of 50 to 180° C., and a reaction time of 1 to 40 min; after microwave treatment, cross-linker-modified graphene is obtained by freeze drying; the conditions for freeze drying are a freezing chamber temperature of -20 to 0° C., an air pressure in the freezing chamber of 100 to 200 Pa, and a drying time of 6 to 48 h.
[0063] Microwave treatment under the above conditions can accelerate the rate of cross-linking agent modification of graphene; by controlling the freeze-drying conditions, the cross-linking agent-modified graphene of the dried product can maintain a good morphological structure and have good stability.
[0064] In some embodiments, in S3, the injection molding conditions are: an injection molding machine injection pressure of 15 to 120 bar, a barrel temperature of 170 to 240° C., a mold temperature of 10 to 60° C., and an injection molding plate thickness of 5 to 500 mm.
[0065] The polyurethane noise reduction coal baffle plate prepared under the above conditions has good mechanical properties and good noise reduction effect.
[0066] In some embodiments, in S3, after injection molding, radiation cross-linking is performed to obtain a polyurethane noise reduction coal barrier. The radiation source for radiation cross-linking is at least one of a high-energy electron beam and Co-60, and the conditions for radiation cross-linking are a radiation dose of 30 to 100 kGy and a radiation rate of 0.1 to 1 kGy / h; the cross-linking density of the polyurethane noise reduction coal barrier after radiation cross-linking is 100 to 500 mol / m 3 .
[0067] By carrying out radiation cross-linking under the above conditions, the wear resistance and strength of the polyurethane noise reduction coal baffle obtained can be further improved.
[0068] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0069] Some of the materials in the embodiments and comparative examples are as follows:
[0070] Polyurethane A: weight average molecular weight 90,000, melt index 2.5 g / 10 min, glass transition temperature 100 ° C, density 1.1 g / cm 3 , melting point 180℃;
[0071] Polyurethane B: weight average molecular weight 100000, melt index 2.0g / 10min, glass transition temperature 125℃, density 1.05g / cm 3 , melting point 190℃;
[0072] Polyurethane C: weight average molecular weight 70,000, melt index 3.0 g / 10 min, glass transition temperature 115 ° C, density 1.2 g / cm 3 , melting point 160℃;
[0073] Polyurethane D: weight average molecular weight 120000, melt index 1.5g / 10min, glass transition temperature 135℃, density 1.08g / cm 3 , melting point 200℃;
[0074] Polyurethane E: weight average molecular weight 60,000, melt index 1.8 g / 10 min, glass transition temperature 70 ° C, density 1.07 g / cm 3 , melting point 140℃;
[0075] Example 1
[0076] An embodiment of the polyurethane noise reduction coal baffle of the present invention, the components of the polyurethane noise reduction coal baffle of this embodiment are shown in Table 1, and the preparation method is as follows:
[0077] S1, adding graphite (microcrystalline graphite) and a dispersant (a compound of N-methylpyrrolidone and sodium dodecylbenzene sulfonate in a mass ratio of 2:1) into ultrapure water to obtain a first mixture, stirring the first mixture for 30 minutes, and then grinding it in a nano-bead mill at a speed of 800 r / min for 1.5 hours to obtain a graphene dispersion, wherein the mass fraction of graphene in the graphene dispersion is 2%, and the mass fraction of the dispersant in the graphene dispersion is 0.03%;
[0078] S2, dissolving a crosslinker (a compound of polyetherimide and polyallylamine in a mass ratio of 1:3) in ultrapure water to obtain a crosslinker solution with a mass fraction of 0.01% of the crosslinker; mixing the graphene dispersion and the crosslinker solution to obtain a second mixture, placing the second mixture in a microwave reactor, modifying the graphene with the crosslinker under the conditions of an output power of 900 W, a reaction temperature of 100° C., and a reaction time of 5 min, and then freeze-drying the graphene, the temperature of the freezing chamber being -15° C., the air pressure in the freezing chamber being 150 Pa, and the drying time being 32 h, to obtain graphene modified with the crosslinker;
[0079] S3, mixing cross-linker-modified graphene, wear resistance agent (a compound of polytetrafluoroethylene and molybdenum disulfide in a mass ratio of 1:5), toughening agent (a compound of natural rubber and polyolefin-based thermoplastic elastomer in a mass ratio of 2:3), processing aid (a compound of dibasic lead phosphite and methyl tin in a mass ratio of 2:1), microbeads (920DET40d25 microbeads) and polyurethane to obtain a third mixture, and injection molding the third mixture at an injection pressure of 20 bar, a barrel temperature of 170°C, and a mold temperature of 10°C to obtain a polyurethane noise reduction coal baffle with a thickness of 10 mm.
[0080] Example 2
[0081] An embodiment of the polyurethane noise reduction coal baffle plate of the present invention, the preparation method of the polyurethane noise reduction coal baffle plate of the present invention is different from that of embodiment 1 only in that a cross-linking treatment is performed after injection molding, specifically as follows:
[0082] The injection molded plate was irradiated with a radioactive source Co-60, with an irradiation dose of 30 kGy and an irradiation rate of 1 kGy / h. The crosslinking density of the polyurethane noise reduction coal retaining plate after irradiation was 120 mol / m 3 .
[0083] Embodiment 3-4
[0084] The embodiments of the polyurethane noise reduction coal baffle of the present invention, embodiments 3 to 4 are different from embodiment 2 only in that the types and proportions of the components in S3 are different, as shown in Table 1.
[0085] Table 1 (parts by weight)
[0086]
[0087]
[0088] Embodiments 5 to 7
[0089] The difference between Examples 5 to 7 and Example 2 is only that the types of toughening agents are different, as follows:
[0090] The toughening agent used in Example 5 is a compound of natural rubber and polyolefin-based thermoplastic elastomer in a mass ratio of 1:4;
[0091] The toughening agent used in Example 6 is natural rubber;
[0092] The toughening agent used in Example 7 is a polyolefin-based thermoplastic elastomer.
[0093] Embodiments 8 to 9
[0094] The difference between Examples 8 to 9 and Example 2 is only that the types of polyurethane are different, as follows:
[0095] The polyurethane used in Example 8 is polyurethane D;
[0096] The polyurethane used in Example 9 is polyurethane E.
[0097] Comparative Example 1
[0098] The only difference between Comparative Example 1 and Example 1 is that the weight portion of the toughening agent is 30 parts.
[0099] Performance Testing
[0100] 1. Tensile performance test: The polyurethane noise reduction coal retaining plate in the embodiment and the comparative example was cut to obtain tensile specimens, and the tensile performance of the plate was tested using a universal tensile machine (model 4403, sensor 100N) of Instron Company of the United States according to the plastic tensile performance test standard ASTM D638-2003 of the American Society for Testing and Materials. Three parallel test samples were tested in each group, and the results were averaged.
[0101] 2. Impact resistance test: The polyurethane noise reduction coal retaining plate in the embodiment and the comparative example was cut to obtain a standard sample, and the impact resistance of the plate was tested using a simple supported beam impact tester (model 9050) of the American Instron Instrument Group according to the plastic impact resistance test standard ASTM D4812-19 of the American Society for Testing and Materials. Three parallel test samples were tested in each group, and the average value was taken.
[0102] 3. Tribological performance test: The wear resistance test of the sample is based on the standard of ASTM G132-96, and the test instrument is HSR-2M high-speed reciprocating friction and wear tester. GCR15 bearing steel ball with a diameter of 5mm is selected as the corresponding material. The steel ball loading load is 20N, the reciprocating frequency is 16.67Hz, the reciprocating length is 5mm, the friction time is 1000min, and 1×106 reciprocating friction cycles are achieved. The tribological properties are studied at room temperature, and the wear amount (M, mg) is measured using a high-precision electronic balance, and the friction coefficient (ε) is calculated using the following formula (1):
[0103]
[0104] Where M1 (mg) is the wear amount of the standard sample, and M2 (mg) is the wear amount of the tested sample.
[0105] The instrument's electronic probe measures wear volume (V, mm 3 ), and use the following formula (2) to calculate the wear rate (K, mm 3 ·N·m -1 ):
[0106]
[0107] Where F(N) is the load during the friction test, and x(m) is the total sliding distance of 30 min. To ensure the accuracy of the experimental data, each sample was tested three times.
[0108] 4. Antistatic performance test: Use 4339A / B type high insulation resistance meter to test the volume resistivity of each sample. Clamp both ends of the sample with copper clips and test according to GB / T1410-2006.
[0109] 5. Sound absorption performance test: A two-channel acoustic impedance tube is used to test the sound absorption coefficient of the sample. The sample thickness is 5mm and the diameter is 30mm. The sound wave frequency range is 100-5000Hz. The test is carried out in accordance with GB / T 18696.1-2004.
[0110] The performance test results are shown in Table 2.
[0111] Table 2
[0112]
[0113]
[0114] It can be seen from Table 1 that the tensile strength and impact resistance of the polyurethane noise reduction coal barrier plates in Examples 1 to 9 are significantly higher than those in Comparative Example 1. The results indicate that the present invention significantly improves the mechanical properties of the polyurethane noise reduction coal barrier plates by selecting the components of the polyurethane noise reduction coal barrier plates, and the polyurethane noise reduction coal barrier plates also have good wear resistance, good sound absorption performance, and excellent antistatic performance, and can effectively dissipate static electricity.
[0115] In addition, by comparing the performance test results of Example 1 and Examples 8 to 9, it can be found that the tensile strength and impact strength of the polyurethane noise reduction coal retaining plate can be significantly improved through radiation cross-linking.
[0116] By comparing the performance test results of Examples 2 to 7, it can be found that when the toughening agent is a compound of the first toughening agent and rubber, and the first toughening agent is at least one of a polyolefin-based thermoplastic elastomer and a bio-based polyol, the comprehensive mechanical properties of the polyurethane noise reduction coal barrier are stronger, and when the mass ratio of the two is (2 to 3): (1 to 3), the strength and toughness of the polyurethane noise reduction coal barrier can be further improved.
[0117] By comparing the performance test results of Examples 2 to 4 with those of Examples 8 to 9, it can be found that when the weight average molecular weight of the polyurethane is 70,000 to 100,000, the melt index is 2 to 3 g / 10 min, and the glass transition temperature is 100 to 130° C., its strength and toughness are significantly higher.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polyurethane noise reduction coal baffle, characterized in that: The invention comprises the following components in parts by weight: 100 parts of polyurethane, 2 to 6 parts of graphene, 0.01 to 0.5 parts of a cross-linking agent, 1 to 8 parts of an anti-wear agent, 5 to 25 parts of a toughening agent, 0.1 to 1 parts of a processing aid, and 1 to 9 parts of micro beads.
2. The polyurethane noise reduction coal baffle according to claim 1 is characterized in that: The mass ratio of the graphene to the toughening agent is (4-6):(5-25).
3. The polyurethane noise reduction coal baffle according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyurethane is 70,000 to 100,000, the melt index is 2 to 3 g / 10 min, and the glass transition temperature is 100 to 130° C.
4. The polyurethane noise reduction coal baffle according to claim 3 is characterized in that: The density of the polyurethane is 1.085-1.293 g / cm 3 , the melting point is 160-190°C; and / or, the crosslinking agent is at least one of polyetherimide, polyallylamine, polydopamine, polyesterimine, trishydroxymethylaminomethane, polystyrene-divinylbenzenesulfonic acid, and γ-aminopropyltriethoxysilane; and / or, the wear-resistant agent is at least one of polytetrafluoroethylene, molybdenum disulfide, polysiloxane, glass fiber, carbon fiber, and aramid fiber; and / or, the processing aid is at least one of dibasic lead phosphite, methyl tin, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 2,6-di-tert-butyl-4-methylphenol; And / or, the microbeads are at least one of organic microbeads and inorganic microbeads.
5. The polyurethane noise reduction coal baffle according to claim 3 is characterized in that: The toughening agent is a compound of a first toughening agent and rubber; the first toughening agent is at least one of a polyolefin-based thermoplastic elastomer and a bio-based polyol; the bio-based polyol is at least one of vegetable oil, starch, and cellulose; the rubber is at least one of natural rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber.
6. The polyurethane noise reduction coal baffle according to claim 5, characterized in that: In the compound, the mass ratio of the first toughening agent to the rubber is (2-3):(1-3).
7. A method for preparing a polyurethane noise reduction coal baffle according to any one of claims 1 to 6, characterized in that: The steps include: S1, adding graphite powder and a dispersant into water to obtain a first mixture, and preparing a graphene dispersion by using a liquid phase shear exfoliation technique on the first mixture; S2, mixing the graphene dispersion with a crosslinker solution to obtain a second mixture, and subjecting the second mixture to microwave treatment to obtain crosslinker-modified graphene; S3, mixing the cross-linking agent-modified graphene, wear-resisting agent, toughening agent, processing aid, microbeads and polyurethane to obtain a third mixture, and injection molding the third mixture to obtain the polyurethane noise reduction coal baffle.
8. The method for preparing the polyurethane noise reduction coal baffle according to claim 7, characterized in that: Includes at least one of the following features: (1) The dispersant is at least one of N-methylpyrrolidone, sodium dodecylbenzene sulfonate, sodium taurodeoxycholate, dimethylformamide, ethanol, o-dichlorobenzene, and poloxamer; the graphite is at least one of microcrystalline graphite, thermal expansion graphite, and highly oriented pyrolytic graphite; (2) The mass fraction of the dispersant in the graphene dispersion is 0.02% to 1%, and the mass fraction of the graphene in the graphene dispersion is 0.5% to 15%; (3) In S1, the liquid phase shear exfoliation technique is performed using at least one of a nano-bead mill, a pin-type sand mill, a turbine sand mill, and a high-pressure homogenizer, and the conditions for the liquid phase shear exfoliation are: 600-3200 r / min, 0.5-5 h; the first mixture is stirred before the liquid phase shear exfoliation technique is performed; (4) The mass fraction of the crosslinking agent in the crosslinking agent solution is 0.01% to 0.5%, and in S2, the volume ratio of the graphene dispersion to the crosslinking agent solution is (5 to 50):1; (5) In S2, the microwave treatment conditions are: output power 350-5000W, reaction temperature 50-180°C, reaction time 1-40min; (6) In S2, after microwave treatment, the cross-linker-modified graphene is obtained by freeze drying; (7) In S3, the injection molding conditions are as follows: an injection molding machine injection pressure of 15 to 120 bar, a barrel temperature of 170 to 240° C., a mold temperature of 10 to 60° C., and an injection molding sheet thickness of 5 to 500 mm.
9. The method for preparing the polyurethane noise reduction coal baffle according to claim 7 or 8, characterized in that: In S3, after injection molding, radiation cross-linking is performed to obtain the polyurethane noise reduction coal baffle.
10. The method for preparing the polyurethane noise reduction coal baffle according to claim 9, characterized in that: The radiation source of the radiation cross-linking is at least one of a high-energy electron beam and Co-60, and the conditions of the radiation cross-linking are a radiation dose of 30 to 100 kGy and a radiation rate of 0.1 to 1 kGy / h.